Associations Between Multiple Leisure Activities, Mental Health and Substance Use Among Adolescents in Denmark: A Nationwide Cross-Sectional Study - Santini, Ziggi Ivan; Meilstrup, Charlotte; Hinrichsen, Carsten; Nielsen, Line; Koyanagi, Ai; Koushede, Vibeke; Ekholm, Ola; Madsen, Katrine Rich (Frontiers in Behavioral Neuroscience, 2020)
Background: Previous research has suggested that leisure activity may benefit mental health and protect against substance use among adolescents, but more research is needed to asses associations with a wide range of outcomes. The aim of this study was to assess associations between multiple leisure activities and 1) mental health outcomes and 2) substance use outcomes in a sample of Danish adolescents. Methods: Using data from the Danish part of the European School Survey Project on Alcohol and Other Drugs (ESPAD) collected in 2019, nation-wide cross-sectional data from 2,488 participants aged 15 or 16 in Denmark were analyzed to assess associations between number of leisure activities and outcomes pertaining to mental health and substance use. Results: Our results show that engaging in multiple activities at least once a week - as compared to one single activity – is associated with increased odds for high mental well-being, and reduced odds for mental health problems. Engaging in multiple activities is also associated with reduced odds for overall substance use and for using substances as a coping method. Among those using substances, engaging in multiple activities is associated with reduced odds of above average substance use. Conclusion: Increasing opportunities for adolescents to engage in leisure activities is suggested to be useful in preventing excessive substance use and promoting mental health. Promoting and increasing access to leisure activities among adolescents could be a promising avenue for policy and practice.